The Comparative Study of The Effectiveness of Seawater Aging with Traditional Techniques and Water Heater Technique for Salt Production - Pasaribu, Roberto Patar; Tanjung, Anasri; Pranoto, Aris Kabul; Ryani, Rani Dewi (PELAGICUS, 2024)
Salt is a product from marine resources which is a strategic commodity as an industrial raw material and food for the community. However, the condition of national salting is currently still not conducive, this is because salt production, both quantity and quality, is still insufficient and sufficient to meet national salt needs. This research aims to compare the effectiveness of traditional techniques and heating techniques in aging seawater for the seawater crystallization process in making salt. With this research, it is hoped that there will be the latest technological innovations to speed up the time for making salt with maintained quality, good quantity and profit so that national salt needs can be met. From this research it can be concluded that the use of heating techniques is more effective than traditional techniques because it can minimize the aging time of sea water and can increase the quantity of salt produced.